2012
DOI: 10.1177/0890334411429114
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of 6-Month Maternal Satisfaction with Breastfeeding Experience in a Multicenter Prospective Cohort Study

Abstract: Although a personally defined experience, successful breastfeeding is usually measured with regard to duration. This study investigated the determinants of maternal satisfaction with breastfeeding experience for 907 mothers enrolled in a prospective cohort study. Despite a median breastfeeding duration (18 weeks) that fell short of recommendations, 822 mothers (90.6%) rated their breastfeeding experience as very or fairly satisfactory. Anticipated breastfeeding duration was a determinant of satisfaction only f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 32 publications
0
21
1
Order By: Relevance
“…The "external" constraints to breastfeeding are already widely explored: inadequate training and support for nursing mother, mother's socioeconomic status/ education/life style, partner's support, inadequate social protection system, etc. (McKinley & Hyde, 2004;Labarère et al, 2012). However, the identified obstacles are not sufficient to address all issues related to a gender dimension on breastfeeding.…”
Section: Resultsmentioning
confidence: 97%
“…The "external" constraints to breastfeeding are already widely explored: inadequate training and support for nursing mother, mother's socioeconomic status/ education/life style, partner's support, inadequate social protection system, etc. (McKinley & Hyde, 2004;Labarère et al, 2012). However, the identified obstacles are not sufficient to address all issues related to a gender dimension on breastfeeding.…”
Section: Resultsmentioning
confidence: 97%
“…In France, another study found percentages of women highly satisfied and satisfied with breastfeeding at 6 months ranging from 88 to 96%, depending on the maternity service analyzed. However, those authors did not use an instrument to measure satisfaction; rather, the outcome was assessed using one single question inquiring about the level of maternal satisfaction with the breastfeeding experience; response options were very unsatisfactory, unsatisfactory, satisfactory, and very satisfactory [8]. A similarly simple approach to the measurement of maternal satisfaction with breastfeeding at 6 months was also recently adopted in Norway, where the investigators found high levels of satisfaction in over 75% of the women assessed [16].…”
Section: Discussionmentioning
confidence: 99%
“…Sample size was calculated using the Programs for Epidemiologists for Windows (WinPEPI) version 11.43. Considering a significance level of 5%, a power of 90%, an estimated prevalence of satisfaction with breastfeeding ranging from 88 to 96% [8] and a minimum prevalence ratio (PR) of 1.25, a minimum sample size of 277 was calculated for variables with a minimum prevalence of 30%.…”
Section: Methodsmentioning
confidence: 99%
“…The physiological barriers mothers may encounter include infant weight loss (Tawia & McGuire, 2014), illness (Academy of Breastfeeding Medicine Protocol Committee, 2009), trouble sucking or latching (Augustin, Donovan, Lozano, Massucci, & Wohlgemuth, 2014;Cottrell & Detman, 2013), perceived reduction in milk flow, increased leaking, and maternal fatigue and pain (J. Labarere et al, 2012). Mothers' breastfeeding behavior may also be affected by maternity leave policies, the ability to express breast milk in social settings (Langellier et al, 2012), needing/wanting to share feeding responsibilities with others, and perceptions about breastfeeding in public ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in a study of mothers' satisfaction with breastfeeding, those who were very or fairly unsatisfied with the breastfeeding experience reported a shorter median duration of breastfeeding (4 weeks) compared to those that were very or fairly satisfied (19 weeks), and tended to indicate physiological experiencerelated barriers such as sucking-related difficulties, painful or cracked nipples, and insufficient milk supply (J. Labarere et al, 2012).…”
Section: Introductionmentioning
confidence: 99%